PENGARUH FLYPAPER EFFECT TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT - Nareswari Adyanindita Kusumawardhani Kusyala; Rudy Badrudin (Jurnal Ekonomi Dan Bisnis, 2023)
ABSTRACT Regional autonomy is carried out to achieve the goals of public welfare for all levels. Local governments prepare the regional revenue and expenditure budgets (APBD) to increase growth that supports public welfare. The purpose of this study is to indentify and analyze the phenomenon of the flypaper effect through the regional original revenue (PAD) and general allocation funds (DAU) on capital expenditure (BM) and then their can effect on economis growth and public welfare through the human development index (IPM). The selected areas in this research cover all regencies and cities in West Java Province. This research takes data on the realization of the regional budget for revenue and expenditure (APBD) at the Directorate General of Fiscal Balance (DJPK) of ministry of finance during the 2016-2020 period. The sampling technique used purposive sampling which resulted 135 data from 18 districs and 9 cities in West Java Province. The test results in this research indicate that PAD nad DAU have positive and significant effect on capital expenditure and show that there is no flypaper effect. The test results also that capital expenditure has positive and significant effect on economic growth, but economic growth is unable to affect public welfare. Keywords: economic growth, welfare, flypaper effect